Health Status and Job Performance of Physical Education Instructors in Higher Education Institutions - Vivencio L. Calixtro Jr. (Indonesian Journal of Educational Research and Technology, 2021)
This study examined the health-related factors to the job performance of physical education (PE) instructors in HEIs of Region XII. It employed a descriptive correlational research design, which includes a survey questionnaire in collecting data from 100 PE instructors. As a result, PE instructors revealed that there is no significant relationship between job performance and physical health status Also, there was no significant relationship between job performance and mental health status. Likewise, there was a significant relationship between job performance and emotional health status. Similarly, there was a significant relationship between job performance and social well-being status. However, there was no significant relationship between job performance and health status since some of the PE instructors are not aware of their health status. The study concluded that the majority of the PE instructors lacked proper self-awareness to sustain healthy wellbeing in teaching PE as a profession.